Surface Engineering Bulletin. (Seattle, WA. SCC Publishing Ltd., 1994)
The surface engineering is a quarterly newsletter dedicated to surface modification technologies. It is being published primarily for circulation among the surface engineering community in India and the ASEAN countries.
Keywords: Engineer -- Periodicals; Surface Engineering -- Periodicals